Community-Based Flood Management on The Bank of The Kelayan River, South Banjarmasin District - Hidayat, Rahmi; Arisanty, Deasy; Alviawati, Eva; Subiyakto, Bambang; Hadi, Rizali (Universitas Lambung Mangkurat, 2024)
Broad knowledge and open thinking are not widely possessed by the community in the Kelayan riverbank area. This study aims to determine the planning of organization, direction, coordination and control to be able to manage community-based floods in the riverbank area. This study uses a descriptive qualitative method with a naturalistic approach. Data were obtained through observation, interviews, and documentation. The data sources obtained through primary data itself which are the subjects of this study include the heads of RT, RW, environmental observers, community leaders and several government officials related to community-based flood management in the area. The research subjects were selected using the Snowball Sampling technique. Data analysis was carried out using narrative and discourse analysis. Based on the results of the study, it was found that planning, organizing and coordination in the Kelayan riverbank community were quite insightful to the community regarding the importance of environmental protection so that natural disasters do not occur, so that organization needs to be considered. Thus, it can be concluded that community-based flood management produces alternatives or solutions so that there is no more flooding in the Kelayan riverbank area, South Banjarmasin District, so that it becomes a safe and comfortable environment to live in.